Strategi Perlawanan Venezuela dalam Menghadapi Tekanan Amerika Serikat melalui ALBA Tahun 2015-2017 - Faradilla Firdaus (Universitas Airlangga, 2019)
Economic and humanitarian crisis that happened in Venezuela since 2014has left Venezuela in international pressure, especially from the UnitedStates. United States pressure make Venezuela position’s isolated in LatinAmerica region also in international. In order facing United Statespressure, Venezuela takes advantage of its position in ALBA as a regionalpower. As ALBA member countries still showing strong support towardsVenezuela despite Venezuela is hit by crisis allegedly due to the failureof socialist economic system on Hugo Chavez’s era. This research usehegemony cooperative theory as analysis instrument which is result threestrategies by Venezuela: (1) balancing reduction strategy by increasebalance of fear towards United States; (2) increasing bandwagoningstrategy towards ALBA member countries to maintain the exsistence ofregional supportive discourse; (3) aggregation power strategy towardsALBA member countries to prevention defection in the region.